Faktor-Faktor Yang Mempengaruhi Struktur Modal Dengan Kepemilikan Manajerial Sebagai Variabel Moderasi - Khosasi, Dian Bravo; Silitonga, Putri S. L.; Firza, Syafira Ulya; Sigalingging, Eni Duwita (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to analyze the influence of liquidity, business risk, asset structure, profitability and company size on the company's capital structure. Apart from that, this research also examines the role of managerial ownership as a moderating variable that can influence the relationship between the independent variable and the dependent variable. This research uses a sample of 603 manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The method used in sampling is based on criteria (purposive sampling). The data collection method in this research uses library research by means of documentation and literature. The results of this research show that liquidity, business risk, asset structure, profitability and company size have no effect on capital structure. Managerial ownership is able to moderate the relationship between company size and capital structure. Managerial ownership is unable to moderate the relationship between liquidity, business risk, asset structure and profitability on capital structure.